Molecular and Histological Identification of Bovine Papillomavirus 1, 2 and a Novel Genotype in Cutaneous Papillomas of Dairy Cattle in Taiwan - Chen, Guan-Shiun; Chiou, Hue-Ying; Chang, Yen-Chen; Liu, Hao-Ping; Pan, Yu-I; Chan, Ming-Yun; Liu, Tsung-Ching; Chia, Ming-Yuan; Huang, Chienjin; Chan, Jacky Peng-Wen; Chang, Chia-Yu (Transboundary and emerging diseases, 2025)
Bovine papillomaviruses (BPVs) are host‐specific and strongly epitheliotropic infectious agents that cause benign epithelial and mucosal proliferations, with potential for malignant transformation. However, BPV1, BPV2, and BPV5 are unique in their ability to infect both epithelial and connective tissues. While BPV infections had been documented globally, there was no disease information reported from Taiwan. To investigate whether BPVs are associated with the development of cutaneous papillomas in dairy cattle in Taiwan, in the present study, eight cutaneous papilloma samples from six dairy farms were collected and analyzed by using histopathology, immunohistochemical (IHC) staining, and molecular biology methods. BPV1 and BPV2 were identified, along with a novel BPV sharing 80.9% sequence identity with BPV38. This novel BPV, classified under Xipapillomavirus , was detected in both epithelial and mesenchymal cells through in situ hybridization (ISH), suggesting a broader tissue tropism than typical Xipapillomavirus infections. These findings provide new insights into BPV diversity and pathogenesis.